2014
DOI: 10.1155/2014/783102
|View full text |Cite
|
Sign up to set email alerts
|

Study of Factors Involved in Tongue Color Diagnosis by Kampo Medical Practitioners Using the Farnsworth‐Munsell 100 Hue Test and Tongue Color Images

Abstract: In traditional Japanese medicine (Kampo medicine), tongue color is important in discerning a patient's constitution and medical conditions. However, tongue color diagnosis is susceptible to the subjective factors of the observer. To investigate factors involved in tongue color diagnosis, both color discrimination and tongue color diagnosis were researched in 68 Kampo medical practitioners. Color discrimination was studied by the Farnsworth-Munsell 100 Hue test, and tongue color diagnosis was studied by 84 tong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Those that received the agreement from all three professionals would be included in this study. According to the literature's reporting, tongue color would be classified into five groups, namely, pale tongue, light red tongue, red tongue, crimson tongue, and purplish tongue (including light purple tongue and blue and purple tongue) [15, 19]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those that received the agreement from all three professionals would be included in this study. According to the literature's reporting, tongue color would be classified into five groups, namely, pale tongue, light red tongue, red tongue, crimson tongue, and purplish tongue (including light purple tongue and blue and purple tongue) [15, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…Oji et al once studied the color discrimination and tongue color diagnosis in 68 traditional Japanese medical practitioners by the Farnsworth-Munsell 100 Hue test and 84 tongue images, respectively, and they found out that overall color discrimination became worse with aging [19]. …”
Section: Introductionmentioning
confidence: 99%
“…So, it is difficult for tongue diagnosis to obtain objective and standardized results. In the past decades, researchers have developed various types of computer-aided tongue diagnosis systems (CATDS) based on computer vision and machine learning to address these problems in many countries [3][4][5][6]. The schematic diagram of a typical CATDS is shown in Figure 1 [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because the description of tongue findings in various books describing tongue diagnosis are diverse and inconsistent, studies about unifying the diagnosis description have been conducted [14], and attempts to standardize tongue diagnosis are being made. It has been reported that it takes more than 10 years of Kampo diagnosis practice to be able to make an accurate diagnosis without being affected by subjective factors such as age and color discrimination ability [15], and it is not easy for doctors with little experience to judge the findings. In order to obtain accurate SB findings on the tongue, quantitative indicators that support diagnosis and systems that can be used in education are necessary.…”
Section: Introductionmentioning
confidence: 99%